2019
DOI: 10.1002/asi.24245
|View full text |Cite
|
Sign up to set email alerts
|

Public health and social media: A study of Zika virus‐related posts on Yahoo! Answers

Abstract: This study investigates the content of questions and responses about the Zika virus on Yahoo! Answers as a recent example of how public concerns regarding an international health issue are reflected in social media. We investigate the contents of posts about the Zika virus on Yahoo! Answers, identify and reveal subject patterns about the Zika virus, and analyze the temporal changes of the revealed subject topics over 4 defined periods of the Zika virus outbreak. Multidimensional scaling analysis, temporal anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Zhang et al [ 49 ] investigated the contents of posts about the Zika virus on Yahoo! Answers, identify and reveal subject patterns about the Zika virus, and analyze the temporal changes of the revealed subject topics over 4 defined periods of the Zika virus outbreak.…”
Section: Analysis Of Covid-19 Trendsmentioning
confidence: 99%
“…Zhang et al [ 49 ] investigated the contents of posts about the Zika virus on Yahoo! Answers, identify and reveal subject patterns about the Zika virus, and analyze the temporal changes of the revealed subject topics over 4 defined periods of the Zika virus outbreak.…”
Section: Analysis Of Covid-19 Trendsmentioning
confidence: 99%
“…For example, Yahoo! Answer includes more than 300 million questions and 90 million unique users worldwide as of 2012 since the service launched in 2005 [ 10 ]. Another popular social Q&A site launched in 2006, Wiki Answers, has 17 million answers posted.…”
Section: Related Literaturementioning
confidence: 99%
“…Answers in English, Baidu Knows in Chinese, and Naver Knowledge-IN in Korean, to exchange information to address their concerns about hearing problems. Prior research has demonstrated that a collection of questions that patients post on social Q&A provides not only interesting but also important information to health professionals [ 9 , 10 , 11 ]. Topic analysis of patients’ questions on the topic of hearing loss allows for achieving a thorough understanding of patients’ perspectives, thereby leading to better development of the patient-centered intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, artificial intelligence (AI) is mainly used to monitor online information propagation rules, [9][10][11] and analyze the influencing factors of online Web texts and infectious disease transmission. [12][13][14] The occurrence of a major public health emergency breaks the public's original psychological balance, which results in a psychological abnormality. As a result, identifying the emotions 15 of netizens can be of tremendous help in promoting public health prevention 16 and health education.…”
mentioning
confidence: 99%